Pengaruh Financial Target, Market Competition, dan Political Connection terhadap Kecurangan Laporan Keuangan - Anggun Yantika; Januar Eko Prasetio (Value : Jurnal Manajemen dan Akuntansi, 2026)
Performance pressure and operational complexity in the raw materials sector heighten vulnerability to financial statement fraud, driven by both internal and external company pressures. This study examines the impact of financial target pressure, market competition dynamics, and political connections on financial reporting fraud in companies. The research population consists of all raw materials sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The sample was determined using purposive sampling with three criteria, yielding 60 company samples. Hypothesis testing was conducted via logistic regression analysis using SPSS version 25. The results reveal that two variables significantly influence financial statement fraud: financial targets, proxied by Return on Assets (ROA), and market competition, measured by the Herfindahl-Hirschman Index (HHI). In contrast, political connections assessed based on the presence of political affiliations within the company show no significant effect. These findings indicate that the demands of meeting financial targets and the intensity of market competition play a primary role in triggering fraudulent behavior, more so than political connections. Nevertheless, financial statement fraud is not solely influenced by the variables examined here but also by other factors not included in this study's model.